Conformationally Restricted β‐Sheet Breaker Peptides Incorporating Cyclic α‐Methylisoserine Sulfamidates. Issue 9 (27th December 2022) - Mazo, Nuria; Navo, Claudio D.; Peccati, Francesca; Andreo, Jacopo; Airoldi, Cristina; Goldsztejn, Gildas; Çarçabal, Pierre; Usabiaga, Imanol; Sodupe, Mariona; Wuttke, Stefan; Busto, Jesús H.; Peregrina, Jesús M.; et al.
Abstract: Peptides containing variations of the β‐amyloid hydrophobic core and five‐membered sulfamidates derived from β‐amino acid α‐methylisoserine have been synthesized and fully characterized in the gas phase, solid state and in aqueous solution by a combination of experimental and computational techniques. The cyclic sulfamidate group effectively locks the secondary structure at the N‐terminus of such hybrid peptides imposing a conformational restriction and stabilizing non‐extended structures. This conformational bias, which is maintained in the gas phase, solid state and aqueous solution, is shown to be resistant to structure templating through assays of in vitro β‐amyloid aggregation, acting as β‐sheet breaker peptides with moderate activity. Abstract : The use of a cyclic sulfamidate moiety as a β‐sheet breaker element is proposed for the first time. The sulfamidate effectively locks the peptide secondary structure in a novel rigid turn both in the gas phase and solid state, which is also maintained in solution. Peptides bearing this motif show moderate amyloid‐β inhibition activity.